Impact of Baseline Total Testosterone Level on Successful Treatment of Sexual Dysfunction in Men Taking Once-Daily Tadalafil 5 mg for Lower Urinary Tract Symptoms and Benign Prostatic Hyperplasia: An Integrated Analysis of Three Randomized Controlled Trials. Issue 5 (1st May 2016) - Mulhall, John P.; Brock, Gerald B.; Glina, Sidney; Baygani, Simin; Donatucci, Craig F.; Maggi, Mario
ABSTRACT: Introduction: Controversy exists as to whether erectile response to phosphodiesterase type 5 inhibitors is compromised in men with low total testosterone (TT) levels. This is amplified by reports of improved response to phosphodiesterase type 5 inhibitor therapy after coadministration of testosterone replacement therapy in hypogonadal men unresponsive to phosphodiesterase type 5 inhibitors. Aim: To determine whether TT and luteinizing hormone levels influence efficacy of tadalafil for erectile dysfunction in men with concomitant lower urinary tract symptoms and benign prostatic hyperplasia. Methods: This integrated analysis included 1, 075 men randomized to once-daily tadalafil 5 mg (n = 540) or placebo (n = 535) for 12 weeks in three prospective clinical trials who had not received concomitant testosterone replacement therapy. Subjects were categorized at baseline by low vs normal TT levels (n = 1, 049; <300 vs ≥300 ng/dL) and normal vs high luteinizing hormone levels (n = 1, 058; ≤9.4 vs >9.4 mIU/mL). Treatment-group differences in International Index of Erectile Function (IIEF) by hormone subgroups were assessed using analysis of covariance. Main Outcome Measures: Changes in IIEF erectile function domain and other domain scores. Results: The overall study population was comprised primarily of white men (>86%) with a mean age range of 64 to 70 years. Median baseline TT level in the integrated population was 355 ng/dL; levels were lower than 300 ng/dL (cutoff for normal) in 32.4% of men. Men with low TT levels reported diabetes (21.8%), cardiovascular disease (54.1%), and hypertension (49.1%) numerically more often than men with normal TT levels (10.6%, 43.2%, and 36.7%, respectively). Low TT and high luteinizing hormone levels were associated with numerically, but not statistically significantly, lower 12-week IIEF domain scores compared with those with normal levels. Changes in most 12-week IIEF domain scores showed that tadalafil was significantly more effective than placebo ( P < .02). Conclusion: Low TT levels at baseline did not negatively influence response to tadalafil in men of advancing age with concomitant lower urinary tract symptoms and benign prostatic hyperplasia and erectile dysfunction.